Cusp-overlap view reduces conduction disturbances and permanent pacemaker implantation after transcatheter aortic valve replacement even with balloon-expandable and mechanically-expandable heart valves - Stephan, Tilman; Krohn-Grimberghe, Marvin; von Lindeiner genannt von Wildau, Annika; Buck, Christoph; Baumhardt, Michael; Mörike, Johannes; Gonska, Birgid; Rottbauer, Wolfgang; Buckert, Dominik (Frontiers in Cardiovascular Medicine, 2023)
Background Conduction disturbances demanding permanent pacemaker implantation (PPI) remain a common complication after transcatheter aortic valve replacement (TAVR).technique led to a reduced rate of PPI when self-expanding valves were used.The aim of the present study was to determine if using the novel COP view is applicable for all types of TAVR prosthesis and results in a higher ID and reduced incidence of new conduction disturbances and PPI.In this prospective case-control study 586 consecutive patients undergoing TAVR with either balloon-expandable Edwards SAPIEN S3 (n=280; 47.8%), or mechanically expandable Boston LOTUS Edge heart valve prostheses (n=306; 52.2%) were included. ID as well as rates of periprocedural PPI and left bundle branch block (LBBB) were compared between the conventional three-cusp coplanar (TCC) projection and the COP view for implantation.Of 586 patients, 282 (48.1%) underwent TAVR using COP, whereas in 304 patients (51.2%) the TCC view was applied. Using COP a significantly higher ID was achieved in Edwards SAPIEN S3 TAVR procedures (ID mean difference -1.0 mm, 95%-CI -1.9 to -0.1 mm; P=0.029), whereas the final platform position did not differ significantly between both techniques when a Boston LOTUS Edge valve was used (ID mean difference -0.1 mm, 95%-CI -1.1 to +0.9 mm; P=0.890). In Edwards SAPIEN S3 valves, higher ID was associated with a numerically lower post-procedural PPI incidence (4.9% vs. 7.3%; P=0.464). Moreover, ID was significantly deeper in patients requiring PPI post TAVR compared to those without PPI (8.7 mm [6.8 -10.6 mm] vs. 6.5 mm [6.1 -7.0 mm]; P=0.005). In Boston LOTUS Edge devices, COP view significantly decreased the incidence of LBBB post procedure (28.1% vs. 47.9%; P<0.001), while PPI rates were similar in both groups (21.6% vs. 25.7%; P=0.396).The present study demonstrates the safety, efficacy and reproducibility of the cusp-overlap view even in balloon-expandable and mechanically-expandable TAVR procedures. Application of COP leads to significantly less LBBB in repositionable Boston LOTUS Edge valves and a numerically lower PPI rate in Edwards SAPIEN S3 valves post TAVR compared to the standard TCC projection. The results should encourage to apply the COP view more widely in clinical practice.